2004
DOI: 10.1021/ma0493832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemistries of Trifunctional Amines on Mechanisms of Michael Addition Polymerizations with Diacrylates

Abstract: The mechanisms of the Michael addition polymerizations of different trifunctional amines with an equimolar 1,4-butanediol diacrylate (BDA) were investigated by using 1H and 13C NMR to in situ monitor the polymerization processes. The trifunctional amine monomers adopted were 1-(2-aminoethyl)piperazine (AEPZ) and 4-(aminomethyl)piperidine (AMPD) and linear aliphatic amines with different steric hindrance on the 2° amines (original), i.e., N-methylethylenediamine (MEDA), N-ethylethylenediamine (EEDA), and N-hexy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 36 publications
11
124
0
Order By: Relevance
“…4-aminomethyl piperidine (AMPD), N-methyl ethylenediamine (MEDA), and 1-(2-aminoethyl) piperazine (AEPZ), with an equimolar diacrylamide. It is found that novel poly(amido amine)s containing secondary and tertiary amines in their backbones are formed as described in Scheme 1, similar to our results obtained for the Michael addition polymerizations of these trifunctional amines with an equimolar diacrylate [25,26]. These novel kinds of poly(amido amine)s are different from those poly(amido amine)s containing only tertiary amines in the backbones, on which Ferruti's group has carried out a systematic investigation [30].…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…4-aminomethyl piperidine (AMPD), N-methyl ethylenediamine (MEDA), and 1-(2-aminoethyl) piperazine (AEPZ), with an equimolar diacrylamide. It is found that novel poly(amido amine)s containing secondary and tertiary amines in their backbones are formed as described in Scheme 1, similar to our results obtained for the Michael addition polymerizations of these trifunctional amines with an equimolar diacrylate [25,26]. These novel kinds of poly(amido amine)s are different from those poly(amido amine)s containing only tertiary amines in the backbones, on which Ferruti's group has carried out a systematic investigation [30].…”
Section: Introductionsupporting
confidence: 85%
“…In our previous work [25,26], we have found that the reactivity of trifunctional amines is unequal in the Michael addition polymerizations with diacrylates, and novel linear poly(amino ester)s applicable for safe and efficient delivery of gene are obtained. Nevertheless, the reactivity sequence of amines and the structures of polymers observed in our works are different from those reported for the polymerizations of trifunctional amines with divinyl sulfone or other diacrylates [27][28][29], so it is necessary to get understanding of the mechanisms of other polymerizations of this category.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the reactivity of the three types of amine in AEPZ has the following sequence: 28 amine (original) > 18 amine > > 28 amine (formed), which agrees with the conclusion in our previous work. [15,16] The difference of reactivity between 28 amine (original) and 18 amine is not so big enough to keep 18 amine intact during the Michael addition reactions. Thus, the reactions between groups A 2 (DVS) and B 3 (AEPZ) yielded a mixture of the addition products DVS-AEPZ and DVS-AEPZ-DVS intermediates at the very beginning of polymerization as shown in Scheme 1.…”
Section: Mechanisms Of the Polymerizationsmentioning
confidence: 99%
“…In the polymerization of this intermediate that is predominant in the polymerization system, the reactivity of the two B 0 amines is different. [15,16] Once one of the two B 0 groups reacts with vinyl groups, a new secondary amine formed can react with vinyl groups further. But its reactivity is much lower than that of the primary amine in AEPZ ring due to steric hindrance of polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, selection of the reaction partners in this fundamentally challenging two-step reaction sequence is crucially important. Although maleimides react with both amines and thiols as Michael donor [124], acrylates are less reactive; at room temperature and without a catalyst, only secondary amines readily react with acrylates [125]. Hence, a reaction mixture of a primary amine, a thiolactone, and an acrylate in the absence of any catalyst results in the formation of the targeted conjugation product.…”
Section: Nucleophilic Amine-thiol-ene Conjugationmentioning
confidence: 99%